Proposta de melhorias do processo de projeto e de desenvolvimento de produtos em empreendimentos imobiliários - Leite, Kelma Pinheiro (2014)
This research addresses, from the lean thinking standpoint, the product development process (PDP) and the project process for multifamily vertical residences of the real estate development market. The concept phase and the production phase became farther apart, so there are numerous professionals employed on different stages and functions, but without proper integration among them. Integration amongst those involved in the construction process improves the quality of the project, adds value and eliminates losses. However, traditional project managing is obsolete because: (1) it does not consider the workflow; (2) it does not consider the predictability of the workflow; and (3) it does not measure the planning system’s performance. To do a project using the lean concept includes a new way of thinking (lean) and incorporates new tools or work methods. Therefore, this paper proposes the following research question: how to improve the project process and the PDP in real estate ventures by applying the philosophy of lean thinking? Aiming at resolving the research question, this paper’s goal is to propose guidelines to increase efficiency of product development process and real estate development’s project process, based on the philosophy of lean thinking. As theoretical basis for this work, a review study was conducted on the literature related to planning methods and control of project process, real estate PDP, on the new production (lean thinking) and project (lean design) philosophy, and also on Building Information Modeling (BIM). This is a qualitative research of applied nature. The research strategy used was an exploratory-descriptive analysis of multiple case studies, which came from cases of development and construction companies that already adopt lean construction in their production process. After the collection and the analysis, guidelines were suggested to improve the project process and the real estate PDP. The applicability of the guidelines is conditioned to the specificities of the companies analyzed here, though not compromising their use in other construction and development companies with similar characteristics. From this paper, other companies can evaluate their maturity level with regards to lean processes and create stages and goals to attain the optimum point of PDP and real estate project design.